Predicting NK cell subsets using gene expression levels in peripheral blood and endometrial biopsy specimens. (3rd August 2017) - Davies, Michael L.; Dambaeva, Svetlana V.; Katukurundage, Dimantha; Repak, Miroslava; Gilman‐Sachs, Alice; Kwak‐Kim, Joanne; Beaman, Kenneth D.
Abstract : Problem: In molecular analysis of tissue biopsy specimens, one crucial aspect is characterization of immune cell populations. This is especially important for evaluation of uterine receptivity by assessing levels of lymphocyte populations including CD56 bright CD16‐ uterine NK cells and CD56 dim CD16+ conventional NK cells. Our objective was to investigate whether measuring total RNA transcripts from a tissue specimen would accurately reflect immune cell levels and be a new technique to assess immune cell subsets. Method of Study: Peripheral blood mononuclear cells (PBMCs) and endometrial tissues were used. Flow cytometry was utilized for the analysis of lymphocyte subsets in PBMCs, and RT‐qPCR was applied to quantify RNA transcripts indicative of lymphocyte and granulocyte populations. Results: In PBMC specimens, there were significant correlations between gene expression levels and cell subsets. NK cells correlated with CD16A, NKp46, and CD56 transcripts, B cells correlated with EBF1, and CD8+ T cells correlated with CD8β. Finally, endometrial tissues displayed high CD56 expression and very low CD3ε, CD16A, and NKp30, reflecting the characteristic endometrial NK cell subsets. Conclusion: Strong correlations between RT‐qPCR data and levels of lymphocyte subsets indicate that gene expression analysis will be a useful technique for characterizing levels of CD56+ cells in endometrial tissues.